The prevalence and sociodemographic determinants of tobacco and nicotine use among students in healthcare disciplines in Saudi Arabian universities: a cross-sectional survey - Aldhahir, Abdulelah M.; Siraj, Rayan A.; Alqarni, Abdullah A.; Alqahtani, Jaber S.; Alyami, Mohammed M.; Majrshi, Mansour S.; Alwafi, Hassan; Alqahtani, Mohammed M.; Monshi, Sarah S.; Al-Zalabani, Abdulmohsen H.; Alanazi, Abdullah M. (Frontiers in Public Health, 2024)
Background Tobacco smoking is one of the most significant health-related problems worldwide. However, the prevalence and sociodemographic determinants of tobacco and nicotine use among students on healthcare courses in Saudi Arabia are limited. Methods This cross-sectional study used a questionnaire that was distributed via SurveyMonkey between November 2022 and June 2023 to all student universities offering healthcare courses. Data are presented as frequency and percentages. The associated sociodemographic factors with current tobacco and nicotine use were subjected to logistic regression. Results Overall, 5,012, of whom 3,872 (77.25%) were males, responded to the online survey. The prevalence of current tobacco and nicotine use was 3,553 (71%). The majority of users used electronic nicotine delivery systems (1,622: 32.36%). The current use of cigarettes (AOR: 1.75 (1.42 to 2.15)), e-cigarettes (AOR: 1.17 (1.01 to 1.37)), and smokeless tobacco substances (AOR: 1.35 (1.02 to 1.90)) were more pronounced among males compared to female students. However, the current use of a hookah was less among males (AOR: 0.74 (95% CI: 61 to 0.91)). Smoking cigarettes was practiced less among students living in other regions compared to the Central Region. However, smokeless tobacco substances seem to be more prevalent in the Western, Southern, and Northern Regions, (AOR: 1.57 (95% CI: 1.09 to 2.26)), (AOR: 1.43 (95% CI: 1.04 to 1.95)), and (AOR: 1.57 (95% CI: 1.09 to 2.26)), respectively. Conclusion Smoking is prevalent among students in the healthcare disciplines, with electronic nicotine delivery systems being the most used product. Several sociodemographic factors were associated with higher tobacco or nicotine use.